Association of the interferon signature metric with serological disease manifestations but not global activity scores in multiple cohorts of patients with SLE. Issue 1 (30th March 2015) - Kennedy, William P; Maciuca, Romeo; Wolslegel, Kristen; Tew, Wei; Abbas, Alexander R; Chaivorapol, Christina; Morimoto, Alyssa; McBride, Jacqueline M; Brunetta, Paul; Richardson, Bruce C; Davis, John C; Behrens, Timothy W; et al.
Abstract : Objectives: The interferon (IFN) signature (IS) in patients with systemic lupus erythematosus (SLE) includes over 100 genes induced by type I IFN pathway activation. We developed a method to quantify the IS using three genes—the IS metric (ISM)—and characterised the clinical characteristics of patients with SLE with different ISM status from multiple clinical trials. Methods: Blood microarray expression data from a training cohort of patients with SLE confirmed the presence of the IS and identified surrogate genes. We assayed these genes in a quantitative PCR (qPCR) assay, yielding an ISM from the IS. The association of ISM status with clinical disease characteristics was assessed in patients with extrarenal lupus and lupus nephritis from four clinical trials. Results: Three genes, HERC5, EPSTI and CMPK2, correlated well with the IS (p>0.96), and composed the ISM qPCR assay. Using the 95th centile for healthy control data, patients with SLE from different studies were classified into two ISM subsets—ISM-Low and ISM-High—that are longitudinally stable over 36 weeks. Significant associations were identified between ISM-High status and higher titres of anti-dsDNA antibodies, presence of anti extractable nuclear antigen autoantibodies, elevated serum B cell activating factor of the tumour necrosis factor family (BAFF) levels, and hypocomplementaemia. However, measures of overall clinical disease activity were similar for ISM-High and ISM-Low groups. Conclusions: The ISM is an IS biomarker that divides patients with SLE into two subpopulations—ISM-High and ISM-Low—with differing serological manifestations. The ISM does not distinguish between high and low disease activity, but may have utility in identifying patients more likely to respond to treatment(s) targeting IFN-α. Clinicaltrials.gov registration number: NCT00962832.